Possible role of glutamine synthetase in the NO signaling response in root nodules by contributing to the antioxidant defenses - Silva, Liliana S.; Carvalho, Helena G. (Frontiers in Plant Science, 2013)
Nitric oxide (NO) is emerging as an important regulatory player in the Rhizobium-legume symbiosis. The occurrence of NO during several steps of the symbiotic interaction suggests an important, but yet unknown, signaling role of this molecule for root nodule formation and functioning. The identification of the molecular targets of NO is key for the assembly of the signal transduction cascade that will ultimately help to unravel NO function. We have recently shown that the key nitrogen assimilatory enzyme Glutamine Synthetase (GS) is a molecular target of NO in root nodules of Medicago truncatula, being post-translationally regulated by tyrosine nitration in relation to nitrogen fixation. In functional nodules of M. truncatula NO formation has been located in the bacteroid containing cells of the fixation zone, where the ammonium generated by bacterial nitrogenase is released to the plant cytosol and assimilated into the organic pools by plant GS. We propose that the NO-mediated GS post-translational inactivation is connected to nitrogenase inhibition induced by NO and is related to metabolite channeling to boost the nodule antioxidant defenses. Glutamate, a substrate for GS activity is also the precursor for the synthesis of glutathione (GSH), which is highly abundant in root nodules of several plant species and known to play a major role in the antioxidant defense participating in the ascorbate/GSH cycle. Existing evidence suggests that upon NO-mediated GS inhibition, glutamate could be channeled for the synthesis of GSH. According to this hypothesis, GS would be involved in the NO-signaling responses in root nodules and the NO-signaling events would meet the nodule metabolic pathways to provide an adaptive response to the inhibition of symbiotic nitrogen fixation by reactive nitrogen species (RNS).